2021
DOI: 10.3390/agronomy11050835
|View full text |Cite
|
Sign up to set email alerts
|

Applications and Development of LEDs as Supplementary Lighting for Tomato at Different Latitudes

Abstract: High-tech greenhouses and artificial light applications aim to improve food production, in line with one of the sustainable development goals of the UN Agenda 2030, namely, “zero hunger”. In the past, the incandescent lamps have been used for supplementary lighting (SL) at higher latitudes to increase greenhouse production during the dark season. Light-emitting diodes (LED) have been replacing gas discharge and incandescent lamps, and their development is expanding SL applications in different agricultural sce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 75 publications
(92 reference statements)
0
12
0
Order By: Relevance
“…Compared with other types of lamps, such as fluorescent, high-pressure sodium (HPS), and metalhalide, LEDs show equivalent or higher luminous efficacy, lack of radiant heat, and longer lifespan (Loi et al, 2021). Besides, LED can also produce the monochromatic light wavelength and make it more convenient to change the light quality constitution in the controlled growing systems (Palmitessa et al, 2021). Understanding how light affects SM biosynthesis is essential for the cultivation of medicinal plants in a controlled environment as well as under open field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other types of lamps, such as fluorescent, high-pressure sodium (HPS), and metalhalide, LEDs show equivalent or higher luminous efficacy, lack of radiant heat, and longer lifespan (Loi et al, 2021). Besides, LED can also produce the monochromatic light wavelength and make it more convenient to change the light quality constitution in the controlled growing systems (Palmitessa et al, 2021). Understanding how light affects SM biosynthesis is essential for the cultivation of medicinal plants in a controlled environment as well as under open field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the 'Carosello leccese' plants grown with LEDs received 1.2 times more radiation than NL conditions (Figure 3). In detail, Palmitessa et al [22] reported that for cucumbers the optimal DLI range varied from 8 to 23 mol•m −2 •d −1 but, equaling the light requirement of 'Carosello leccese' with those of the cucumber, during this experiment the level of DLI NL fell below the optimal values around 40 DAT (Figure 3). In fact, as shown in Figure 4, if the production under different light treatments did not vary significantly until 40 DAT, after this period the 'Carosello leccese' plants grown under LEDs produced more than the plants grown only with NL (Figure 4).…”
Section: Supplementary Light Management and Its Effects On 'Carosello Leccese' Yield And Fruit Qualitymentioning
confidence: 52%
“…flexuosus [11]) was cultivated in the greenhouse with a soilless system during the fall period. Following recent studies regarding the success of light-emitting diodes (LEDs) application as a supplementary light (SL) system in Mediterranean greenhouse conditions for tomato crops [22,23], we investigated the effects of this technology/technique on 'Carosello leccese' growth/yield, as a way to increase extra-seasonal fruit production. Finally, through the morphological and biochemical analysis of the fruits, the aim of this study was also to evaluate the main qualitative and nutritional characteristics of 'Carosello leccese', paying attention to the biochemical composition of the parts that make up the edible part of the fruits.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, El Youssfi et al [31] found that, using a soilless system technique, it is possible to obtain a yield comparable (or higher) to that obtained with traditional techniques (22 t•ha −1 on average). Furthermore, the recent achievement regarding the development of artificial light technologies [32] and their positive effects on crop performances in the Mediterranean regions [10,11] inspired our research activity, applying different SL spectra supplied with LED technology to green bean cultivation. As was shown on Table 1, the results were encouraging, because the green bean plants grown under LEDs produced 16% more edible product than under natural light conditions, but the number of the pods did not vary between light conditions (Table 1).…”
Section: Discussionmentioning
confidence: 99%